Factors Influencing the Acceptance of Endoscopic Thyroidectomy Via Oral Vestibular Approach (ETOVA) by Thyroid Surgery Candidates. Issue 5 (24th October 2022) - Zhou, Xuezhi; Deng, Jiejie; Xiong, Jing; Xia, Daojing; Liu, Tao; Li, Xingqin; Duan, Yuling; Huo, Jinlong; Wang, Cunchuan; Qu, Rui
Abstract : Objective: To investigate the factors affecting the acceptance of endoscopic thyroidectomy via the oral vestibular approach (ETOVA) in Chinese patients before thyroid surgery. Methods: The enrolled patients were asked to answer a questionnaire postoperatively about their demographics, medical insurance coverage, sources of information, reasons for selection, and safety. The relationship between the collected data and the acceptance of ETOVA was analyzed. Results: Two hundred patients (40 males, 20%; 160 females, 80%) answered the questionnaire. One hundred sixty-two of them (81%) accepted ETOVA. Univariate analysis showed that the patients' age, cosmetic effect, safety, results perception, and recommendations from family, friends, doctors, and nurses are correlated with the acceptance of ETOVA. Multivariate analysis showed that patients' age (OR=0.966, P =0.015), cosmetic effect (OR=12.620, P =0.000), safety (OR=0.295, P =0.016), minimal invasion (OR=4.877, P =0.001), and doctors/nurses' advance (OR=4.485, P =0.017) are statistically significant and were positively correlated with the acceptance of ETOVA. Education level, medical insurance coverage, family support, past surgical history, and operative-related symptoms were not statistically significant ( P >0.05). Conclusion: Among thyroid surgery candidates in Southwest China, younger patients with cosmetic requirements and minimally invasive procedures desires are more likely to consider ETOVA at the urging of their physicians/nurses. Providing appropriate healthcare education, medical insurance coverage, and information options for surgical treatments is vital to improving patients' acceptance of ETOVA.